Involvement of P2X7 purinergic receptor and MEK1/2 in interleukin-8 up-regulation by LL-37 in human gingival fibroblasts - Montreekachon P. (2014)
Background and Objective: The antimicrobial peptide LL-37, derived from human neutrophils, can directly chemoattract leukocytes and up-regulate the expression of several immune-related genes in various cell types. In this study, we wanted to determine the immunoregulatory effect of LL-37 on interleukin-8 (IL-8) expression in human gingival fibroblasts (HGFs) and to characterize intracellular signaling pathway(s) and receptor(s) involved in IL-8 induction. Material and Methods: Cultured fibroblasts were treated with different concentrations of LL-37 or interleukin-1β (IL-1β), as a positive control, for specific periods of time in the presence or absence of various inhibitors. RT-PCR and real-time PCR were conducted to analyze the expression of IL-8 mRNA, and the IL-8 levels in cell-free culture media were measured using ELISAs. The MTT assay was performed to determine the cytotoxicity of LL-37. Results: Nontoxic concentrations of LL-37 (up to 10μm) and IL-1β significantly up-regulated the expression of IL-8 mRNA in a dose-dependent manner (p<0.05). The IL-8 protein levels were consistently significantly elevated in conditioned media of LL-37-treated HGFs (p<0.05). IL-8 up-regulation by LL-37 was completely abrogated by 20μm U0126, consistent with transient phosphorylation of p44/42 MAP kinases. Moreover, pretreatment with Brilliant Blue G (a selective antagonist of the P2X7 receptor) and the neutralizing antibody against P2X7 blocked IL-8 up-regulation in a dose-dependent manner, consistent with expression of the P2X7 receptor in HGFs. Conclusion: These findings indicate that LL-37 induces IL-8 expression via the P2X7 receptor and the MEK1/2-dependent p44/42 MAP kinases in HGFs, suggesting both direct and indirect involvement of LL-37 in neutrophil recruitment into an inflammatory site within diseased periodontal tissues. © 2011 John Wiley & Sons A/S.